CLOUD COMPUTING: TEORI DAN IMPLEMENTASINYA DALAM DUNIA BISNIS DAN PEMASARAN - Sudaryono Sudaryono; Diah Aryani; Ira Tyas Ningrum (CCIT Journal, 2012)
Cloud computing is a technology that utilizes the internet services using a central server with the goal of maintaining a virtual nature of data and applications. The presence of cloud computing will obviously lead to changes in the workings of information technologysystems within an organization. This is because the concepts of cloud computing through virtualization, standardization and other fundamental features can reduce information technology costs, simplify the management of information technology services, andaccelerating service delivery. In general, cloud computing architecture consists of: (1) Infrastructure as a Service (IaaS), (2) Platform as a Service (PaaS), and (3) Software as a Service (SaaS). Characteristics of cloud computing are: (1) self-service (on demand self service), (2) broadband access (broadband access network), (3) clustered resource (resource pooling), (4) elastic (rapid elasticity), and (5) measured service (measuredservice). While the advantages of cloud computing is: (1) without any initial investment, (2) convert CAPEX into OPEX, (3) flexible and easily developed, (4) focus on the business, rather than information technology, and (5) of control and responsibility of service. Withcloud computing consumers free themselves from the responsibility for managing the stack of computing resources. Levels ranging from SaaS when it is completely free, PaaS while still must make an application, and IaaS are still busy with the operating system. Thiscontrasts with On-Premise to take care of all your own.